The Effect of Elastic Tape on Lower Extremity Muscle Activity in Squats of Young Female Adults: A Cross-sectional Pilot Study - Namjeong Cho; Yangrae Kim (Korean Research Society of Physical Therapy, 2023)
Background: In terms of physical performance, elastic tape (ET) is known to contribute to injury prevention and performance enhancement. Objects: This study aimed to compare and analyze the effect on lower extremity muscle activity of young adult women with and without ET during squats. Methods: In this study, six healthy, young women were recruited as participants in a university laboratory. Participants were allocated to two groups of three after measuring muscle activity in a pre-test, and the experiment was conducted for a total of two weeks (two sessions). First, 10 half squats were taped once in the first week, and 10 half squats were performed without taping in the second week. The other group did this in reverse and measured muscle activity after the squat was over. Results: As a result of this study, there was no significant difference in the quadriceps with or without ET (Z = -0.11, p > 0.05). Similarly, no significant difference was found in hamstring (Z = -0.31, p > 0.05). Conclusion: No beneficial effect was found on changes in muscle activity following ET application during squats. Further studies require randomized controlled trials that increase the number of participants and the intensity of the intervention, and measure pain, function, and performance rather than muscle properties depending on the biomechanical lifting mechanism.